ANALYSIS OF OIL TRANSERSTERIFICATION OPTIMIZATION IN BIODIESEL PRODUCTION - Ghassan Hassan, Abdul Razzaq, Jasim I. Humadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Production of oilseed under country currently goes just 60 to 70% of their overall needs of edible oil & remaining has been via extracts. Reduction of edible oil has been to big under country & still important product does not satisfied needed count of edible oil & requirements has been extracted & hence it was not allowed to forward sources for production of biodiesel. On other side, resources of non edible oil may solution regards production og biodiesel. In this paper transesterification process optimization & observations of biodiesel through Pongamia & neem oils has been presented. Basis on optimized protocol regards production through oils of non edible regards Pongamia & neem via transesterification catalyzed utilizing ratio of 1.6 oil methanol at 60oC, 0.7gm catalyst, 600rpm speed & 2hrs time. Biodiesel through these resources has been observed simultaneously regards characterization of quantitative & qualitative.